Strengthening Family Knowledge on the Care of Patients with Hallucinations Through Mental Health Education - Mesa, Nofita Dewi Kok; Arisjulyanto, Dedy; Muspitha, Fitri Dia; Kusuma, Ardhanari Hendra; Kurniawan, Fajar Bakti; Payasan, Lalu Guntur (PT. LARPA JAYA PUBLISHER, 2026)
Mental health disorders remain a significant public health concern in Indonesia due to their increasing prevalence and substantial impact on individuals, families, and communities. These disorders can impair a person's ability to think clearly, regulate emotions, behave appropriately, and interact effectively with others. Among the various symptoms experienced by individuals with mental disorders, hallucinations are one of the most common and challenging because they can interfere with daily functioning and increase the risk of relapse if not properly managed. Families play a crucial role in supporting patients through appropriate care, supervision, and adherence to treatment. Therefore, improving family knowledge about hallucination management is essential to enhance patient outcomes. This community service activity aimed to strengthen the knowledge of families and patients regarding the care and management of hallucinations at the Abepura Mental Hospital (RSK Abepura). The activity was conducted through direct mental health education and counseling sessions involving interactive lectures, discussions, and question-and-answer sessions. A total of 63 participants, consisting of patients and their family members visiting the hospital, took part in the program. The evaluation demonstrated that approximately 75% of participants actively engaged in the educational sessions, showed high enthusiasm, and were able to correctly answer the evaluation questions, indicating an improvement in their understanding of hallucination management. These findings suggest that mental health education is an effective strategy for enhancing family knowledge and supporting better care for patients with hallucinations.